A Model Planning For Slum Residential Areas To Become Fast Growing Areas In Medan City - Suci Astari (SEAN Institute, 2023)
The aim of national development is to achieve community welfare while considering regional aspects and economic policies. One strategy involves harnessing the resources in slum areas. Among these, the slum areas in the northern part of Medan City, including Medan Belawan, Medan Labuhan, and Medan Marelan Districts, hold potential for development. The research employs both qualitative and quantitative methods. Qualitative approaches are used to describe the potential of the slum areas in Medan City, while quantitative methods are employed to analyze the feasibility of transforming these areas into fast-growing zones. To turn these slum areas into economically supportive regions, comprehensive planning is essential to tap into their potential. One way to actualize this plan is by designating the slum areas in Medan City as Minapolitan Areas.